Calidad de vida en 1947 - Velázquez, Guillermo Ángel (2020)
With a view to presenting an overview of the socio-spatial differences that characterised the country around the middle of the 20th century, this chapter analyses the quality of life of the population during the Fourth National Census of the Argentine Republic, at a departmental level. There were significant inequalities in this indicator in 1947, with the most populated provinces standing out for having the highest quality of life values (Buenos Aires, Córdoba and Santa Fe), as opposed to those in the north. In this sense, it should be noted that these spatial differences, for the vast majority of social and economic indicators, are the same as those observed today.